Capturing seasonal variations in faecal nutrient content from tundra herbivores using near infrared reflectance spectroscopy - Mathilde Defourneaux; Laura Barbero-Palacios; Jonas Schoelynck; Noémie Boulanger-Lapointe; James D.M. Speed; Isabel C. Barrio (Science of The Total Environment, 2025)

Long-term changes in herbivore community and vegetation impact of wild and domestic herbivores across Iceland - Mathilde Defourneaux; Isabel C. Barrio; Noémie Boulanger-Lapointe; James D. M. Speed (Ambio, 2024)
Changes in wild and domestic herbivore populations significantly impact extensive grazing systems, particularly in low productive environments, where increasing wild herbivore populations are perceived as a threat to farming. To assess the magnitude of these changes in Iceland, we compiled time series on herbivore populations from 1986 to 2020 and estimated changes in species densities, metabolic biomass, and consumption of plant biomass in improved lands and unimproved rangelands. We compared estimates of consumption rates to past and present net primary production. Overall, the herbivore community composition shifted from livestock to wildlife dominated. However, wild herbivores only contributed a small fraction (14%) of the total herbivore metabolic biomass and consumption (4–7%), and livestock dominated the overall herbivore biomass. These insights highlight the necessity of developing improved local integrated management for both wild and domestic herbivores where they coexist.

Reliability of baseline self-reported information in the AGRICAN cohort - Séverine Tual; Clémentine Lemarchand; Johanna Giovannini; Mathilde Boulanger; Matthieu Meryet-Figuiere; Madar Talibov; Bénédicte Clin; Rémy Morello; Isabelle Baldi; Pierre Lebailly (Cancer Causes & Control, 2022)

Gender differences in respiratory health outcomes among farming cohorts around the globe: findings from the AGRICOH consortium - Jonathan Fix; Isabella Annesi-Maesano; Isabelle Baldi; Mathilde Boulanger; Soo Cheng; Sandra Cortes; Jean- Charles Dalphin; Mohamed Aqiel Dalvie; Bruno Degano; Jeroen Douwes; Wijnand Eduard; Grethe Elholm; et al. (Journal of Agromedicine, 2021)

Occupational exposure to pesticides and multiple myeloma in the AGRICAN cohort - Séverine Tual; Amandine Busson; Mathilde Boulanger; Marine Renier; Clément Piel; Camille Pouchieu; Romain Pons; Stéphanie Perrier; Noémie Levêque-Morlais; Patrick Karuranga; Clémentine Lemarchand; Elisabeth Marcotullio; et al. (Cancer Causes & Control, 2019)

Agricultural exposure and risk of bladder cancer in the AGRIculture and CANcer cohort - Mathilde Boulanger; Séverine Tual; Clémentine Lemarchand; Anne-Valérie Guizard; Michel Velten; Elisabeth Marcotullio; Isabelle Baldi; Bénédicte Clin; Pierre Lebailly (International Archives of Occupational and Environmental Health, 2017)